HOLISTIC MARKETING AND SUSTAINABILITY: INSIGHTS FROM A BIBLIOMETRIC ANALYSIS OF GLOBAL RESEARCH - Khan, Wahiduzzaman; Farhan, Kazi Ahmed; Hossain, Md. Belal (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
Sustainability has grown into vital focus in global business practices, with companies increasingly integrating sustainable strategies into their marketing approaches. However, research on the convergence of sustainability and holistic marketing still needs to be completed, especially in emerging economies. A cohesive understanding is necessary for businesses to adopt comprehensive strategies that serve both financial and ecological objectives. This study investigates global research trends in incorporating sustainability into holistic marketing. Using a bibliometric analysis, data from 105 peer-reviewed articles published between 1996 and 2024 were analyzed and sourced from Scopus through the PRISMA framework. Visualization tools like VOSviewer were used to map co-authorship networks, keyword co-occurrence, and citation patterns. The results reveal that sustainability is increasingly becoming a focal point in marketing strategies, with significant contributions from developed economies like the United States and the United Kingdom, while emerging economies like India are gradually entering the discourse. The co-occurrence analysis identified four key thematic clusters: sustainability and innovation, marketing and product development, corporate social responsibility (CSR) and supply chain management, and decision-making processes. The findings of this study indicate a growing alignment between sustainability and holistic marketing, particularly in innovation and product development. However, the research remains concentrated in developed regions, highlighting the need for more studies in emerging markets. The results suggest a need for greater collaboration between areas to foster a more global approach to sustainable marketing practices.JEL Classification Codes: M31, Q01, M14.